Alterations in hippocampal somatostatin interneurons, GABAergic metabolism, and ASL perfusion in an aged male mouse model of POCD aggravated by sleep fragmentation - Li, Yun; Yu, Jiafeng; Yang, Ningzhi; Long, Siwen; Li, Yize; Zhao, Lina; Yu, Yonghao (Physiological reports, 2024)
Sleep fragmentation (SF) is increasingly recognized as a contributing factor to postoperative cognitive dysfunction (POCD). Given the critical roles of somatostatin (SST) interneurons, associated gamma‐aminobutyric acid (GABA)ergic neurotransmitters, and hippocampal perfusion in sleep‐related cognition, this study examined changes in these mechanisms in preoperative SF affecting POCD induced by anesthesia/surgery in aged male mice. The Morris water maze (MWM), novel object recognition (NOR), and Y maze tests were utilized to evaluate POCD. Arterial spin labeling (ASL) was employed to measure hippocampal regional cerebral blood flow (rCBF). In vitro assays quantified the levels of GABAergic metabolites—such as SST, neuropeptide Y (NPY), glutamic acid decarboxylase 1 (GAD1), vesicular GABA transporter (VGAT), and GABA and the distribution of SST interneurons in the hippocampus through enzyme‐linked immunosorbent assay and immunofluorescence. Preoperative 24‐h SF exacerbated anesthesia/surgery‐induced spatial memory impairments observed in the MWM, NOR, and Y maze tests. Preoperative 24‐h SF significantly increased the number of SST interneurons in hippocampal CA1, elevated hippocampal levels of SST, NPY, GAD1, and GABA, and reduced the rCBF. Preoperative SF aggravated POCD in aged male mice, with an increased number of SST interneurons in hippocampal CA1, elevated hippocampal GABAergic metabolites, and a further reduction in rCBF. Preoperative 24‐h sleep fragmentation aggravates anesthesia/surgery‐induced POCD in aged mice, accompanied by an increase in the number of SST interneurons in the hippocampal CA1 region, an increase in the levels of hippocampal SST, NPY, GAD1, and GABA, and a decrease in hippocampal ASL perfusion, as well as hippocampal neuron damage.